Conhecendo e reconhecendo simultaneamente frações ordinárias, números decimais e porcentagens - Oliveira, Raquel Gomes de [UNESP]; Gomes, Leomar Aparecido Santos [UNESP]; Ceresini, Vitor Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The project is justified by the unsatisfactory performance in Mathematics of students who complete the first grades of basic education, prevailing in the ratings as the School Performance Evaluation System of the São Paulo State (SARESP) and has the following objectives: 1) diagnosing the knowledge students of the 6th year on the concepts of common fractions, decimals and percentages; 2) develop and implement teaching strategies that simultaneously work with these concepts; 3) enable to students the development and expansion of mathematical skills and attitudes and 4) enable to the students of Mathematics Teacher Education of the FCT-Unesp, opportunity to develop pedagogical knowledge in applying teaching and learning strategies in tune with the environment school. In 2013 and 2014, part of its objectives have been reached specifically those that refer to the future Mathematics teacher, this because as consequences of goals 1 and 2 was designed and implemented a diagnostic assessment of the mastery of the concepts of common fractions, decimals and percentages . The results of the diagnostic evaluation supported the elaboration of an educational booklet that oportunizasse students the simultaneous learning of these concepts, their representations and contextualization. The pedagogical work with this didactic booklet is being developed and it will be evaluated in 2015.

O projeto tem como justificativa insatisfatórios desempenhos em Matemática dos alunos que terminam as séries iniciais da Educação Básica, prevalecendo nas avaliações como no Sistema de Avaliação de Rendimento Escolar do Estado de São Paulo (SARESP) e possui como objetivos: 1º) diagnosticar o conhecimento de alunos do 6º ano sobre os conceitos de frações ordinárias, números decimais e porcentagens; 2º) desenvolver e implementar estratégias de ensino que trabalhem simultaneamente esse conceitos; 3º) possibilitar a esses alunos o desenvolvimento e a ampliação de habilidades e atitudes matemáticas e 4º) possibilitar a alunos do curso de Licenciatura em Matemática da FCT-Unesp, oportunidade de desenvolver saberes pedagógicos ao aplicarem estratégias de ensino e aprendizagem em sintonia com o ambiente escolar. Em 2013 e 2014, parte de seus objetivos foram atingidos alcançados especificamente aqueles que se referem aos alunos bolsistas, isto porque enquanto consequências dos objetivos 1 e 2 foi elaborada e aplicada uma avaliação diagnóstica sobre o domínio dos conceitos de frações ordinárias, números decimais e porcentagens. Os resultados da avaliação diagnóstica subsidiaram a elaboração de uma apostila didática que oportunizasse aos alunos a aprendizagem simultânea desses conceitos, suas representações e contextualizações. O trabalho pedagógico com essa apostila didática está em desenvolvimento neste ano de 2015.
Keywords: Fraction; Decimal number; Percentage; Fração; Número decimal; Porcentagem